Building competitive advantage through platform-based product family thinking: Case powerpacks - Jukka Ohvanainen; Esa Hietikko (Journal of Industrial Engineering and Management (JIEM), 2011)
Purpose: The purpose of this paper is to discuss through the main aspects and principles of successful platform-based product family development and management. For example car industry and car manufacturers take advantage of platform-based product families while solving the conflict of balancing between wide product variety and operational efficiency. This is a common dilemma also in some other manufacturing companies operating on versatile markets; how to serve individual customer needs with minimum development, manufacturing and service efforts? Product families are in this paper seen as an answer. Thus, the aim of this paper is to promote the adoption of often complex and risky product family development especially in technology and manufacturing focused companies. To be able to minimize risks and maximize the advantages companies need to understand the dynamics of the product family thinking presented in this paper. Design/methodology/approach: After a literature survey the main aspects and principles of the product family thinking are illustrated through a case example from a company designing and manufacturing hydraulic piling equipment. Findings: The case study shows that as universal practices are missing the "best practice" in product family development is always dependent on the nature of the company and its products. It is also evident that gaining long-term competitive advantage through product family thinking will not happen without continuous learning and investments in both time and resources. Originality/value: This paper presents the main aspects and principles of the platform-based product family thinking in a systematic and hierarchical manner by connecting together platforming, architecture design, strategic aspects and management perspectives.
Keywords: 650; Product family; product platform